Proximal humeral interlocking system plate for pediatric subtrochanteric femur fracture: a case report - Mankar, Pratik; Pundkare, Gopal (International Journal of Research in Orthopaedics, 2023)
Hip fractures are rare in the pediatric age group and they contribute about 1% of all fractures in children. Subtrochanteric femur fractures are the rarest form of hip fractures in children. The treatment for children between the ages 6-12 years is controversial. The treatment options for pediatric subtrochanteric femur fracture include traction followed by hip spica cast, immediate spica casting, cast bracing, internal fixation and external fixation. We report a case of a subtrochanteric femur fracture in a 7-year-old girl following a fall of heavy object over her leg. The fracture was fixed with an adult 3.5 mm proximal humeral interlocking system (PHILOS) plate. The purpose of this report is to provide an alternative mode of management for paediatric subtrochanteric femur fracture.